Magnetism and fermiology of kagome magnet YMn6Sn4Ge2 - Hari Bhandari; Rebecca L. Dally; Peter E. Siegfried; Resham B. Regmi; Kirrily C. Rule; Songxue Chi; Jeffrey W. Lynn; I. I. Mazin; Nirmal J. Ghimire (npj Quantum Materials, 2024)
Abstract Kagome lattice magnets are an interesting class of materials as they can host topological properties in their magnetic and electronic structures. YMn6Sn6 is one such compound in which various exotic magnetic and electronic topological properties have been realized. Here, by means of a partial substitution of Sn with an isovalent and slightly smaller atom Ge, we demonstrate the sensitivity of such chemical substitution on the magnetic structure and its influence in the electronic properties. Magnetic structure of YMn6Sn4Ge2 determined by neutron diffraction reveals an incommensurate staggered magnetic spiral with a slightly larger spiral pitch than in YMn6Sn6. This change in magnetic structure influences the Fermi surface enhancing the out-of-plane conductivity. Such a sensitivity to the partial chemical substitution provides a great potential for engineering the magnetic phases and associated electronic properties not only in YMn6Sn6, but also in the large family of 166 rare-earth kagome magnet.